"Possible answers:
\(\displaystyle{f{{\left({x}\right)}}}=\frac{{1}}{{x}}\) & \(\displaystyle{g{{\left({x}\right)}}}=\frac{{1}}{{x}}+{3}\)

\(\displaystyle{f{{\left({x}\right)}}}=\frac{{1}}{{{x}+{2}}}\) & \(\displaystyle{g{{\left({x}\right)}}}=\frac{{1}}{{{x}+{2}}}+{3}\)

\(\displaystyle{f{{\left({x}\right)}}}=\frac{{2}}{{{x}-{1}}}\) & \(\displaystyle{g{{\left({x}\right)}}}=\frac{{2}}{{{x}-{1}}}+{3}\)

\(\displaystyle{f{{\left({x}\right)}}}=\frac{{1}}{{{x}+{2}}}\) & \(\displaystyle{g{{\left({x}\right)}}}=\frac{{1}}{{{x}+{2}}}+{3}\)

\(\displaystyle{f{{\left({x}\right)}}}=\frac{{2}}{{{x}-{1}}}\) & \(\displaystyle{g{{\left({x}\right)}}}=\frac{{2}}{{{x}-{1}}}+{3}\)